Contact Analysis of Involute Cylindrical Gear with Considering Assembly Error - Yandong Shi; Ruiliang Zhang (Jixie chuandong)
When spur gear pair meshing with the assembly error，it will cause the edge contact and stress concentration，and affect the service life. In the meantime，because the parallelism error of vertical plane will produce a larger deviation of tooth contact，therefore，taking the spur gear pair with the parallelism error of vertical plane as the research object，then based on the systematic introduction of the numerical calculation theory of gear contact stress，and the contact stress，contact width and the corresponding load distribution coefficient along the tooth in the case of different assembly error and load conditions are calculated，and the results calculated by numerical calculation method and national standard calculation method in the case of no assembly error are made a comparative analysis. The results show that the results calculated by two methods in the case of no assembly error are close to each other，and the numerical calculation result can reflect the edge effect of the gear pair meshing. Under the same load，with the increase of the installation error，the uneven contact in the tooth width direction becomes worse，and one side disconnects. Under the same assembly error，the uneven contact is improved with the increase of load，the maximum contact stress presents nonlinear increase with the increase of assembly error and load.